It's more than just cancer biology: Health disparities in patients with pancreatic neuroendocrine tumors. Issue 8 (9th September 2021) - Underwood, Patrick W.; Riner, Andrea N.; Neal, Dan; Cameron, Miles E.; Yakovenko, Anastasiya; Reddy, Sushanth; Rose, John Bart; Hughes, Steven J.; Trevino, Jose G.
Abstract: Background and Objectives: Pancreatic neuroendocrine tumors (PNETs) represent a rare form of pancreatic cancer. Racial/ethnic disparities have been documented in pancreatic ductal adenocarcinoma, but health disparities have not been well described in patients with PNETs. Methods: A retrospective review of patients with PNETs in the National Cancer Database was performed for 2004–2014. Approximately 16 605 patients with PNETs and available vital status were identified. Survival was compared by race/ethnicity and socioeconomic status using Kaplan–Meier methods and Cox regression. Results: There were no significant differences in survival between Non‐Hispanic, White; Hispanic, White; or Non‐Hispanic, Black patients on univariate analysis. Kaplan–Meier analysis showed that patients from communities with lower median household income and education level had worse survival ( p < 0.001). Patients age less than 65 without insurance, similarly, had worse survival ( p < 0.001). Multivariable modeling found no association between race/ethnicity and risk of mortality ( p = 0.37). Lower median household income and lower education level were associated with increased mortality ( p < 0.001). Conclusions: Unlike most other malignancies, race/ethnicity is not associated with survival differences in patients with PNETs. Patients with lower socioeconomic status had worse survival. The presence of identifiable health disparities in patients with PNETs represents a target for intervention and opportunity to improve survival in patients with this malignancy.